A methods engineering study on Pilipinas Hino, Incorporated - Balucan, John Paul; Amis, Monnaliz; Bescara, Honeylet (Diliman, Quezon City College of Engineering, 2001)
Pilipinas Hino, Incorporated is a manufacturing company producing different models of buses, trucks, and Suzuki vehicles. Focusing on the buses, the group initially observed and studied the company's present system. After gathering preliminary data, the group was able to cite few problem areas in the system. The areas of concern were high percentage of rejected/damaged seats, inefficient facility layout-chassis assembly and painting and trimming section, lack of concern on the part of contractual workers, delay in production due to late deliveries of raw materials and inefficient location of the PDI section. After preliminary analysis on the areas of concern, the group determined and verified which problems greatly affect the process and those that were feasible. The group focused on giving solutions to the high percentage of damaged seats, inefficient layout and concern on the part of contractual workers. Few alternatives were generated through careful study and further data gathering. Mobile racks were designed for storage of seats while waiting for use, few changes in the facility layout were presented-reversion of the chassis assembly line, interchanging of the painting and trimming section and the relocation of the PDI section and a buddy system regarding the problem for the lack of concern of contractual workers on the quality of their work. Costs, time duration and other details were discussed on the implementation plan. The other problem areas were recommended for further study together with the alternatives presented but were not given the "go" signal due to impracticality and having trivial effects on the company compared to its cost.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering.
Keywords: Systems analysis